Gender and Age as Correlates of Stigmatization of Psychiatric Patients Among Health Care Workers in Neuropsychiatric Hospital, Enugu Enugu State - Anike, Anthony Ifeanyi, Anike, Anthony Ifeanyi (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The study examined gender and age as Correlates of Stigmatization of Psychiatric Patients among Health Care Workers in Neuropsychiatric Hospital, Enugu Enugu State. In order to accomplish the purpose of the study, a descriptive correlational survey research design was employed to determine the Correlates of Stigmatization among Health Care Workers in Neuropsychiatric Hospital, Enugu. The population for the study consisted of all Health Care Workers in Neuropsychiatric Hospital, Enugu. There was no sample based on the fact that the population (n =179) was manageable. The instrument for data collection was researcher-designed questionnaire titled Correlates of stigmatization of psychiatric patients’ questionnaire (COSPQ). The result shows among others a very low correlation between HCWs’ gender(r=.017,p=.581), age(r=.223,p=.294) and stigmatization of psychiatric patients except for one of the components (separation) of stigmatization under gender that showed low correlation. The finding also shows that both the null hypotheses of no significant relationship between HCWs’ gender(R=.000, p=.993), age(R=.027, p=.029) and stigmatization of psychiatric patients were acceptable. This implies that gender, age of the HCWs’ respectively cannot be used to predict stigmatization of psychiatric patients.